2016
DOI: 10.1103/physreve.93.051101
|View full text |Cite
|
Sign up to set email alerts
|

Photofocusing: Light and flow of phototactic microswimmer suspension

Abstract: We explore in this paper the phenomenon of photofocusing: a coupling between flow vorticity and biased swimming of microalgae toward a light source that produces a focusing of the microswimmer suspension. We combine experiments that investigate the stationary state of this phenomenon as well as the transition regime with analytical and numerical modeling. We show that the experimentally observed scalings on the width of the focalized region and the establishment length as a function of the flow velocity are we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 14 publications
(26 reference statements)
2
31
0
1
Order By: Relevance
“…While our theoretical predictions agree with the numerical results obtained in Ref. [20] showing a jet insta-bilities for pullers in the absence of diffusion, we note that in contrast a recent experimental realisation of focused puller suspensions (specifically, the green alga Chlamydomonas) did not display such axial clustering [23]. The origin of this discrepancy could for instance come from the existence of a threshold in flow intensity such as the one observed in Ref.…”
Section: Discussionsupporting
confidence: 82%
“…While our theoretical predictions agree with the numerical results obtained in Ref. [20] showing a jet insta-bilities for pullers in the absence of diffusion, we note that in contrast a recent experimental realisation of focused puller suspensions (specifically, the green alga Chlamydomonas) did not display such axial clustering [23]. The origin of this discrepancy could for instance come from the existence of a threshold in flow intensity such as the one observed in Ref.…”
Section: Discussionsupporting
confidence: 82%
“…The coarse-grained phototactic drift and the effective diffusivity can be used in a Keller-Segel-like continuum model of the phototactic behaviour of a population of CR, in the spirit of previous effective descriptions of phototaxis [38,41,42]. In this model, valid sufficiently far from the source, the local concentration of cells c(ρ, t) moving in the fibre's axisymmetric light field I(ρ) obeys the continuity equation…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the swimming characteristics of motile phytoplankton, there have been various theoretical, numerical and experimental studies (Durham et al 2009(Durham et al , 2013Pedley et al 1988;Pedley and Kessler 1990;Son et al 2015), with focus on the swimming behaviors of Chlamydomonas reinhardtii (Martin et al 2016;Sineshchekov et al 2000), Chlamydomonas nivalis (Hill and Häder 1997), Heterosigma akashiwo (Durham et al 2009(Durham et al , 2013 and Volvox (Drescher et al 2009;Goldstein 2015). Two types of models, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lillo et al (2014) reported the influences of acceleration of flow on the formation of algal patches in a rotating cylindrical tube. Martin et al (2016) observed the focusing of C. reinhardtii in the flow through a microchannel under the combined action of vorticity and phototaxis. Rusconi et al (2014) found that the flow shear hampered the chemotaxis of Bacillus subtilis.…”
Section: Introductionmentioning
confidence: 99%